ヒョウカイ ナイ カイヨウ カンソク ニ モチイル アイスフェンス ノ シサク - 高橋, 邦夫; タカハシ, クニオ; 飯田, 高大; イイダ, タカヒロ; 橋田, 元; ハシダ, ゲン; 小達, 恒夫; オダテ, ツネオ; Takahashi, Kunio T.; Iida, Takahiro; Hashida, Gen; Odate, Tsuneo (2012)
P(論文) 南極観測船「しらせ」は世界有数の砕氷能力を持つことから,通常の調査船では困難である定着氷域や流氷域での海洋観測が可能である.しかし,これまで氷海内では海氷の存在により観測測器を用いることが困難であった.第52次日本南極地域観測隊より,これまでの海洋生態系モニタリング観測をさらに氷海内においても実施することとなり,観測測器を海氷からガードするアイスフェンスを用いることで,海氷による観測機器の破損やプランクトン試料へのダメージを抑えることに成功した.本稿では,アイスフェンスの改良と現場での観測の概要について,また有用性や今後の改良点について報告する. The powerful ice-breaking capability of the Japanese icebreaker Shirase raises the possibility of marine observations in the fast-ice and/or permanent ice zone; however, it has been difficult to use conventional equipment in such areas due to the risk of damage by sea-ice. The marine biological monitoring program in the sea-ice area off Syowa Station was started during the 52nd Japanese Antarctic Research Expedition to overcome the difficulties encountered when performing conventional oceanographic observations. The program employs ＂ice-fence＂ (diameter: 1000 mm, height: 700 mm, stainless-steel), which has been successful in protecting the observation equipment (e.g., plankton nets and CTDs) from damage by sea-ice. This report describes the results of field tests of the performance of ＂ice-fence＂ for oceanographic observations in sea-ice areas. Possible improvements to the system are also suggested. departmental bulletin paper